Emotional Labor in the Care Field and Empathy-enhancing Education by Reading Literature: A Brief Review - Jonggab KIM (Tehran University of Medical Sciences, 2018)
Background: Nursing is not just task-based work, but also emotional work. Nurses are also obliged to satisfy patients' emotional needs, which often results in burnout and depression. We aimed to propose an effective method for reducing their emotional burden.  Methods: We took theoretical measure to verify some theories on emotion and emotional labor. Results: Empathy can be enhanced by reading literature. It has been recognized from ancient times that reading is an empathic experience in its very essence. Reading is not possible without the reader identifying and sympathizing with the character in the story. Conclusion: Reading literature is not only an efficient means of enhancing empathy, but also very practical to implement. Among programs that proved efficient are role exchange programs, here-and-now spontaneity, perspective taking, simulation exercises, and so on. The problem with them is that they require special facilities and equipment. If they are not available, reading practice would be the best alternative.